Strategic brand management - Elliott, Richard H. (Oxford University, 2018)
A brand is not merely a representation of a product: it is an emotional and symbolic perception we develop that influences our thoughts, feeling, and behavior. Strategic Brand Management is the only textbook to go beyond the standard branding models to fully explore this perception and consider brands as truly sociocultural phenomena. The book's innovative framework separates a brand's concept into its functional and emotional parts to give students a complete understanding of how brands operate and how they compete for consumer loyalty.